Consumer-Driven Quality Improvement of Tofu Sumedang: An Integrated Kano–QFD Approach for Strategic Product Development - Pujianto, Totok; Mardawati, Efri; Agustien, Shilvya Dewi (Industria: Jurnal Teknologi dan Manajemen Agroindustri, 2024)
AbstractSumedang tofu is an Indonesian traditional food with unique characteristics and high cultural value. The product quality in the market still varies, especially regarding tofu's sensory and safety attributes. This study aimed to identify and analyze the quality attributes of Sumedang tofu based on consumer perceptions to formulate relevant technical improvement priorities. The approach integrated the Kano model and Quality Function Deployment method in a systematic analytical framework. The study involved 30 respondents at the Sumedang Tofu Restaurant "Sari Kedele" Sumedang Regency, West Java Province, Indonesia. The identification results showed that 37 quality attributes were obtained from the Voice of Customer and classified into the Must Be, One-Dimensional, and Attractive categories. Attributes such as crispy crust texture (importance score 4.55), served freshly fried (4.64), and attention to cooking oil usage (4.53) were the primary concerns. The House of Quality Matrix showed that worker training (score 857.3), consumer serving (767.0), and raw material sorting (566.5) were the technical responses with the highest contribution to satisfaction. This study result indicated that consumer perception is important in quality improvement strategies. Implementation of this integrative model supports measurable decision-making, strengthens competitive advantage, and maintains local product sustainability.Keywords: consumer perception, Kano model, product quality, Quality Function Deployment, Sumedang tofu Abstrak Tahu Sumedang merupakan pangan tradisional Indonesia yang memiliki karakteristik unik dan nilai budaya tinggi. Mutu produk yang beredar di pasaran masih bervariasi, terutama pada atribut sensoris dan keamanan. Penelitian ini bertujuan mengidentifikasi dan menganalisis atribut mutu tahu Sumedang berdasarkan persepsi konsumen untuk merumuskan prioritas perbaikan teknis yang relevan. Pendekatan yang digunakan adalah integrasi model Kano dan metode Quality Function Deployment dalam satu kerangka analitis yang sistematis. Penelitian melibatkan 30 responden aktif di Restoran Tahu Sumedang “Sari Kedele”, Kabupaten Sumedang, Provinsi Jawa Barat, Indonesia. Hasil identifikasi menunjukkan bahwa 37 atribut mutu diperoleh dari Voice of Customer dan diklasifikasikan ke dalam kategori Must Be, One-Dimensional, dan Attractive. Atribut seperti tekstur kulit renyah (4,55), penyajian dalam keadaan panas (4,64), dan perhatian terhadap minyak goreng (4,53) menjadi perhatian utama. Matriks House of Quality menunjukkan bahwa pelatihan karyawan (857,3), penyajian ke konsumen (767,0), dan sortasi bahan baku (566,5) adalah respon teknis dengan kontribusi tertinggi terhadap kepuasan. Hasil penelitian ini menunjukkan bahwa persepsi konsumen penting dalam strategi peningkatan mutu. Implementasi model integratif ini mendukung pengambilan keputusan yang terukur, memperkuat keunggulan kompetitif, dan menjaga keberlanjutan produk lokal.Kata kunci: model Kano, mutu produk, persepsi konsumen, Quality Function Deployment, tahu Sumedang